Survei Daya Tahan Aerobik Atlet Shorinji Kempo Tanah Laut Kategori Randori - Rahmayanti, Rahmayanti; Amirudin, Akhmad; Arifin, Ramadhan (Institut Teknologi Bandung, 2024)
Endurance is the first factor in determining the performance of Randori athletes because the long competition system makes endurance very necessary.This research method uses survey research using data collection techniques using tests and measurements with quantitative descriptive methods. The population in this study were all 25 Tanah Laut shorinji kempo athletes in the randori category. The sample in this study was 15 Randori athletes who often took part in training activities. The sampling technique in this research used a purposive sampling technique. The data collection technique uses the Multistage Fitness Test (MFT). Results from the Aerobic Endurance test of the Shorinji kempo Tanah Laut Athlete Randori Category with a total of 15 male and female athletes in categories, namely 4 athletes in the very poor category with a presentation of 26.7%, 3 athletes in the poor category with a presentation of 20%, 7 athletes with a sufficient category with a presentation of 46.7%, 1 athlete in the good category with a presentation of 6.6% can be concluded that the aerobic endurance of the Tanah Laut shorinji kempo athlete in the randori category is in the sufficient category. Suggestions for athletes to be able to participate in training activities regularly according to the schedule determined by the coach so that endurance can improve better and also for coaches to be able to build enthusiasm, motivate and vary training activities so that athletes continue to train so they don't get bored in the training activities. carried out routinely.